PENGARUH KUALITAS LAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN NASABAH MOBILE BANKING BRI STUDI KASUS KELURAHAN DI LEBAK BULUS - Aditya Nugroho; Gojali Supiandi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to analyze the influence of service quality and trust on customer satisfaction among BRI mobile banking users in Lebak Bulus Village. The research employed a quantitative method with an associative approach and a saturated sampling technique. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, linear regression, and hypothesis testing. Validity test results showed that the calculated r value exceeded the r table value of 0.194, while the reliability test produced a Cronbach’s Alpha value above 0.60, indicating reliable variables. The normality test indicated a significance value of 0.200, which exceeded 0.05. Multicollinearity testing showed a tolerance value of 0.78 and a VIF of 1.282. Autocorrelation and heteroscedasticity tests indicated no violations of assumptions. The t-test and F-test results demonstrated that service quality and trust have a positive and significant effect on customer satisfaction in the context of digital banking services